Metode Technology Acceptance Model (TAM) Dalam Analisis Tingkat Kepuasan Pengguna Transportasi Umum Terhadap Aplikasi TJ : Transjakarta - yopi handrianto; Ilham Thomas Saputra (Reputasi: Jurnal Rekayasa Perangkat Lunak, 2025)
Abstract - Transjakarta is the first Bus Rapid Transit (BRT) transportation system in Southeast and South Asia managed by PT Transportasi Jakarta. Some time ago, in an event PT Transportasi Jakarta issued a new innovation, namely the TJ : Transjakarta. The purpose of this study is to analyze how the level of satisfaction of public transportation users with the TJ : Transjakarta application. The research problem approach used is the technology acceptance model (TAM) model with the variables used are Perceived ease of Use, Perceived Uselfulness, Actual System Usage, Behavioral Use and Attitude Toward Using. The data collection method used is a questionnaire distributed via Google Form. The results of the questionnaire were processed using SPSS 30.0. From the results of data analysis that has been done, it is concluded that the Perceived Ease of use variable has the most significant influence on user satisfaction. Based on the results of the simultaneous analysis, it shows that the variables Perceived Ease of use (X1), Perceived Usefulness (X2), Behavioral Intention to Use (X3), and Actual System Usage (X4) simultaneously positively affect Attitude Toward Using (user satisfaction) (Y) with a percentage level of influence of 67.1%. This means, there is an influence on the satisfaction of public transportation users who use the TJ : Transjakarta application. Keywords : Technology Acceptance Model (TAM), User Satisfaction, TJ : Transjakarta